Republic of Haiti - Public Expenditure Management and Financial Accountability Review (PEMFAR) : Improving Efficiency of the Fiscal System and Investing in Public Capital to Accelerate Growth and Reduce Poverty - World Bank (Washington, DC, 2012)
After the lost decade 1994-2004, marked by political instability and economic decline, Haiti has reformed significantly and revived growth, especially in the past three years. Macroeconomic policies implemented since mid-2004 helped restart economic growth, reestablish fiscal discipline, reduce inflation and increase international reserves. Financial sector stability has been maintained though weaknesses have emerged. Significant progress was also achieved in the implementation of economic governance measures, mainly in the area of legal framework, core public institutions and financial management processes and procedures. Notably, basic budget procedures were restored, the public procurement system strengthened, and anti-corruption efforts stepped up. Efforts were also made to improve efficiency and transparency in the management of public enterprises. These recent political and economic developments open a window of opportunity to break with Haiti's turbulent past and create the sound foundations for strong and sustained economic growth and poverty reduction. In such an environment, the development challenge of more dynamic growth in order to reduce poverty requires bold policy actions across a broad spectrum covering various areas of Government interventions to: (i) improve security; (ii) expand and improve the quality of the infrastructure base; (iii) expand the economic base and (iv) enhance human capital. But because of Haiti's scarce resources, prioritizing Government interventions is critical to ensure that public resources are allocated to their best uses. This calls for reforms to improve efficiency of public spending. However, public expenditure reforms would not be enough to decisively put Haiti on a strong and sustained growth path unless they are complemented by revenue-enhancing measures. This implies that the country design a comprehensive fiscal reform package. Major policy lesson from this experiment is that strong and sustainable growth depends on the scope and quality of the fiscal reforms. Fiscal reforms should target a broad-based fiscal package, which aims at expanding the fiscal space and improving efficiency in the allocation of public spending. This package would combine: (a) an increase in total public investment; (b) a reallocation of public spending to investment; (c) a crease in the effective indirect tax rate; (d) an increase in direct tax rate; (e) an increase in security spending; and (f) a reduction in collection costs. The Haiti macro-model shows that the fiscal package tends to have positive impact on growth and poverty over time. Foreign aid could play a catalytic role to foster fiscal reforms and help accelerate growth in the short and medium-term.